Changes in Social Relations in Rural Communities Due to the Influx of Digital Technology and New Media - Suhardi, Asmara Juana (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study examines the changes in social relations within rural communities as a result of the influx of digital technology and new media. Over the past decade, rural areas have experienced significant shifts in their social fabric due to the increasing accessibility and usage of digital platforms, smartphones, and internet connectivity. The rapid growth of new media has altered communication patterns, social interactions, and community structures, leading to both positive and negative consequences. This research aims to explore how these technological advancements have transformed traditional social relations in rural settings, focusing on changes in communication, social integration, and cultural practices. Through qualitative interviews, case studies, and field observations in various rural communities, this study highlights key transformations in interpersonal relationships, community participation, and the negotiation of identity within the digital age. The findings suggest that while new media facilitates greater access to information, global networks, and economic opportunities, it also challenges local traditions, exacerbates generational divides, and creates digital divides among community members. Additionally, the role of digital platforms in reshaping power dynamics and social hierarchies within rural communities is critically analyzed. The results provide valuable insights into how digital technology is reconfiguring rural life, suggesting that these communities face unique challenges and opportunities in adapting to a rapidly changing technological landscape. This study contributes to the understanding of rural-urban dynamics in the digital era and offers recommendations for policymakers, community leaders, and social organizations to manage these transformations in ways that promote inclusive growth and social cohesion.